Cellular Self-Structuring and Turbulent Behaviors in Atmospheric Laminar Channels - Roșu, Iulian-Alin; Nica, Dragos-Constantin; Cazacu, Marius Mihai; Agop, Maricel (Frontiers in Earth Science, 2022)
Assimilating the atmosphere with multifractal entities, nonlinear behaviors in the framework of scale relativity theory regarding its hydrodynamic functionality are established at various scale resolutions. From this perspective, revealing a “hidden” symmetry of the specific multifractal force with the SL (2, R) group leads to synchronization of atmospheric entities based on operational procedures (differential and integral Riemann-type geometries, harmonic mappings from Euclidian to hyperbolic space, variational principles, and others) that imply cellular self-structuring, laminar channels, and singularities as turbulence generators. These behaviors can then be assimilated and compared with recent discoveries regarding laminar channels found in atmospheric turbulence through lidar data processing.